Development of Learning Tools with Learning Videos Using the Flipped Classroom Approach on Gas Kinetic Theory Material in Class XI SMA - Sukma Raviasta; Zulhelmi Zulhelmi; Zuhdi Ma’aruf (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2020)
This research’s goal was to develop learning tools with video using a flipped-classroom approach which is valid on the kinetic theory of gas for students in class XI MIPA SMA. This research uses a research and development method with the ADDIE development model (analysis, design, development, implementation, and evaluation), which in this research is limited to the development phase. The research instrument used was a problem-fulfillment questionnaire filled out by students and a validation assessment sheet that was filled in by a validator. The data collection technique was based on the results of filling out a questionnaire by students at SMA N 1 Pekanbaru and from the validation analysis sheet by the validator. The data analysis technique used the percentage method and continued with data validation using descriptive analysis. This research produces learning tools in the form of lesson plans, student worksheets, and learning videos. The results of the assessment of learning tools using the flipped classroom approach obtained an average value for lesson plans with a very high category value of 4.36, video learning with a value of 4.56 in the very high category, and LKPD with a score of 4.2 very high categories. Each assessment indicator has a value greater than 3, and the validity value is declared valid. Thus, the learning device using video media using the flipped-classroom approach to the kinetic theory material of gas for students of class XI MIPA SMA is declared to be valid and suitable for use.